Yeast Biodiversity from DOQ Priorat Uninoculated Fermentations - Padilla, Beatriz; García-Fernández, David; González, Beatriz; Izidoro, Iara; Esteve-Zarzoso, Braulio; Beltran, Gemma; Mas, Albert (Frontiers in Microbiology, 2016)
Climate, soil and grape varieties are the primary characteristics of terroir and lead to the definition of various appellations of origin. However, the microbiota associated with grapes are also affected by these conditions and can leave a footprint in a wine that will be part of the characteristics of terroir. Thus, a description of the yeast microbiota within a vineyard is of interest not only to provide a better understanding of the winemaking process but also to understand the source of microorganisms that maintain a microbial footprint in wine from the examined vineyard. In this study, two typical grape varieties, Grenache and Carignan, have been sampled from four different vineyards in the DOQ Priorat winegrowing region. Afterward, eight spontaneous alcoholic fermentations containing only grapes from one sampling point and of one variety were conducted at laboratory scale. The fermentation kinetics and yeast population dynamics within each fermentation experiment were evaluated. Yeast identification was performed by RFLP-PCR of the 5.8S-ITS region and by sequencing D1/D2 of the 26S rRNA gene of the isolates. The fermentation kinetics did not indicate clear differences between the two varieties of grapes or among vineyards. Approximately 1,400 isolates were identified, exhibiting high species richness in some fermentations. Of all the isolates studied, approximately 60 % belong to the genus Hanseniaspora, 16 % to Saccharomyces and 11 % to Candida. Other minor genera, such as Hansenula, Issatchenkia, Kluyveromyces, Saccharomycodes and Zygosaccharomyces, were also found. The distribution of the identified yeast throughout the fermentation process was studied, and Saccharomyces cerevisiae was found to be present mainly at the end of the fermentation process, while Aureobasidium pullulans was isolated primarily during the first days of fermentation in three of the eight spontaneous fermentations. This work highlights the complexity and diversity of the vineyard ecosystem, which contains yeasts from different species. The description of this yeast diversity will lead to the selection of native microbiota that can be used to produce quality wines with the characteristics of the Priorat.